Rural Roads Infrastructure and Agricultural Products Distribution: A Focus on Akure South Local Government Area, Ondo State, Nigeria - Eniola, Olaogbebikan Jimoh; Osas, Iyare (International Journal of Business, Economics and Management, 2017)
This study assesses the effects of Rural Road Infrastructure on the distribution of Agricultural products in Akure South Local Government area with a view to providing solutions to the problems caused by inadequate provisions of road infrastructure and its negative impact on agricultural product distributions in the study area. The study evaluated the opinion of the farmers, traders, drivers who are the users of rural roads as well as the government officials in charge of rural road maintenance and construction. Furthermore primary data were employed in eliciting information from the respondent through the questionnaires and systematic random sampling techniques were employed in gathering relevant data and information within the study area. The result of the analysis revealed a significant relationship at 0.05 between the quality of the road infrastructure and the transportation of agricultural product in the study area at p-0.02 and r-0.186. The study concluded that the roads in the study area as well as those connecting the farms with markets are bad and recommended that these roads should be widened and bituminized as well as the provisions of other road infrastructure and the member of the community should participate in rural roads construction and maintenance.